Sistema toyota de produção: um estudo na linha de produção em uma indústria de confecção de ternos - Ricci, Mayara Rohenkohl (2013)
The garment sector has been growing in recent years, this is due to increased demand for products offered consequently growth, industries need to adapt to demand. Some industries needs new employees, others want to increase the yield with the number of employees you already have. The clothing industry under study currently works with male social clothing, is located in West Paraná and only works for orders. But the existing production does not meet demand desired, requiring studies and analyzes. To this must be analyzed balancing production and layout of the sews process. The studies were performed on the layout, the times of operations and line balancing, on the theory proposed by the Toyota Production System which are analyzes of transport losses. The theory shows that the minimization of this loss occurs by studying of the layout and there is a need to balance the line with the aid of the times of the operations, which are the times of the employees who perform them. First, the study showed that there is distance from one job to another. Already, the balancing shows that some jobs are balanced and not others, causing idleness. Bringing as proposed two ways to reduce the transportation indoor the industry, first arrange the layout of how the balancing suggests and the second shows an improvement in the layout according to the existing layout. Through this study it was possible to observe the paths traversed along the production process and currently there are disadvantages in the process, as there are idleness among employees. The new proposal for the layout created are a physical arrangement by process, then the jobs are closer to each other with no observed loss per carriage.